Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1128/jvi.00588-19
|View full text |Cite
|
Sign up to set email alerts
|

Cellular DNAJA3, a Novel VP1-Interacting Protein, Inhibits Foot-and-Mouth Disease Virus Replication by Inducing Lysosomal Degradation of VP1 and Attenuating Its Antagonistic Role in the Beta Interferon Signaling Pathway

Abstract: DnaJ heat shock protein family (Hsp40) member A3 (DNAJA3) plays an important role in viral infections. However, the role of DNAJA3 in replication of foot-and-mouth-disease virus (FMDV) remains unknown. In this study, DNAJA3, a novel binding partner of VP1, was identified using yeast two-hybrid screening. The DNAJA3-VP1 interaction was further confirmed by coimmunoprecipitation and colocalization in FMDV-infected cells. The J domain of DNAJA3 (amino acids 1 to 168) and the lysine at position 208 (K208) of VP1 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 63 publications
3
39
0
Order By: Relevance
“…RNA virus: YFV 350 Immunity modulation RNA virus: HFDV 354 Cellular transformation DNA virus: HBV, [363][364][365][366] Small chaperone Hsp27 Viral replication RNA virus: EV-A71, 384 Swine fever virus (CSFV), 388 Porcine epidemic diarrhoea virus (PEDV) 389 DNA virus: Adenovirus, 390 HSV-1, 397 Virus entry and uncoating RNA virus: Newcastle disease Virus, 402 DEGV [402][403][404] DNA virus: SV40 413 RT virus: HIV 407,410 Virus translation RNA virus: EV-A71 415 Oxidative stress and ER stress RNA virus: Influenza, 419 HCV, 421 EMCV, 422 435 Coronavirus, 436 Poliovirus, 438 HCV 437 DNA virus: HCMV 488 RNA transcription DNA virus: HPV18, 425,489 HBV, 490 HSV 492 RT virus: HIV 514 RNA polyadenylation RT virus: Rous sarcoma virus 485,486 (HDAC6/8) in the influenza RdRp nuclear import stage. HDAC6/8 inhibitors efficiently limit the polymerase nuclear import and suppress virus replication.…”
Section: Protein Maturationmentioning
confidence: 99%
“…RNA virus: YFV 350 Immunity modulation RNA virus: HFDV 354 Cellular transformation DNA virus: HBV, [363][364][365][366] Small chaperone Hsp27 Viral replication RNA virus: EV-A71, 384 Swine fever virus (CSFV), 388 Porcine epidemic diarrhoea virus (PEDV) 389 DNA virus: Adenovirus, 390 HSV-1, 397 Virus entry and uncoating RNA virus: Newcastle disease Virus, 402 DEGV [402][403][404] DNA virus: SV40 413 RT virus: HIV 407,410 Virus translation RNA virus: EV-A71 415 Oxidative stress and ER stress RNA virus: Influenza, 419 HCV, 421 EMCV, 422 435 Coronavirus, 436 Poliovirus, 438 HCV 437 DNA virus: HCMV 488 RNA transcription DNA virus: HPV18, 425,489 HBV, 490 HSV 492 RT virus: HIV 514 RNA polyadenylation RT virus: Rous sarcoma virus 485,486 (HDAC6/8) in the influenza RdRp nuclear import stage. HDAC6/8 inhibitors efficiently limit the polymerase nuclear import and suppress virus replication.…”
Section: Protein Maturationmentioning
confidence: 99%
“…To better understand the potential pathogenic consequences of VP1-host protein interactions, we performed a yeast two-hybrid (YTH) assay as previously described and reported that VP1 interacted with host DnaJ heat shock protein family member A3 (DNAJA3) and showed that DNAJA3 played an essential role for suppression of FMDV replication (7). In the present study, we report that FMDV VP1 interacted with host ribosomal protein SA (RPSA), a component of the ribosome (8,9).…”
mentioning
confidence: 74%
“…FMDV structural VP1 protein interacted with porcine host protein RPSA. Cellular RPSA was identified as a potential target of FMDV VP1 by YTH assay in our previous study (7). To confirm the VP1-RPSA interaction, we performed the coimmunoprecipitation assay.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the interaction of the host cell protein DnaJ heat shock protein family (Hsp40) member A3 (DNAJA3) with VP1 was identified through a yeast two-hybrid system. Studies has shown that DNAJA3 can significantly reduce the inhibitory effect of VP1 on SeV-induced IRF3 phosphorylation, dimerization, and nuclear localization through the lysosomal pathway, thus reducing the antagonism on the IFN-β signal pathway and inhibiting FMDV replication ( Zhang et al, 2019 ). In addition, VP1 can also act on ribosomal protein SA (RPSA) to weaken its inhibitory effect on the mitogen-activated protein kinase (MAPK) pathway, which is conducive to the FMDV replication ( Zhu et al, 2020 ).…”
Section: Fmdv Proteins Regulate Host Innate Immunitymentioning
confidence: 99%